Comparative study of dexmedetomidine and clonidine as an adjunct to levobupivacaine in transversus abdominis plane block in patients undergoing total abdominal hysterectomy: a randomized control study - Gupta, Bharti; Gupta, Amit; Verma, R. K.; Shah, Payal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Ultrasound guided TAP block is safe, simple and effective method of providing postoperative analgesia in surgeries involving abdominal wall incision by blocking anterior branches of thoracolumbar nerves originating from T6-L1. Our aim to study the efficacy of dexmedetomidine and clonidine as an adjunct to levobupivacaine in ultrasound guided TAP block for postoperative analgesia in patients undergoing TAH. Methods: Prospective, double blind randomized control study. Ninety ASA I and II patients scheduled for TAH were randomly assigned in a double blinded study and divided into three groups. Group L received 18ml of 0.25% levobupivacaine+2ml of NS to make total volume of 20ml on each side. Group LC and Group LD received 18ml of 0.25% levobupivacaine + 1 mcg/kg of clonidine or dexmedetomidine diluted in NS to make total volume of 20ml on each side. USG guided TAP block was given when subarachnoid block level regressed to T10 level. Postoperatively patients were assessed for pain scores, HR, SBP, DBP, nausea vomiting, sedation and satisfaction scores at 0, 2, 4, 6 and 12 and 24 hours. Statistical analysis was performed using SPSS software 17. p value<0.05 was considered significant. Results: Pain scores were significantly lower in LD and LC groups as compared to L group and demand for first rescue analgesic was delayed in LD group (491.50±73.29min) and group LC (268.00±35.47min) as compared to group L (129.17±10.67min). The total number of demand doses in 24 hours were significantly less in group LD (1.00±0.00) followed by group LC (2.03±0.18) and group L (2.77±0.57) respectively. Incidence of hypotension, bradycardia and sedation was more in LD group as compared to LC and L groups. Conclusions: TAP block with dexmetomidine as an adjunct to levobupivacaine provides prolonged postoperative analgesia as compared to clonidine as an adjunct and plain levobupivacaine.